Dose-response association of sleep duration with anxiety symptoms in Chinese type 2 diabetes mellitus - Shang,Wenlu; Li,Yan; Sun,Yanli; Pan,Ruiping; Dang,Yuqi; Wen,Jing; Wang,Liqun (PeerJ, 2024)
Objectives Anxiety is a disorder with a high prevalence in T2DM, and some studies have found that sleep problems can cause anxiety. Therefore, this study explored the independent effects of night sleep duration on anxiety symptoms in T2DM patients. Research Design and Methods A cross-sectional population-based study was conducted using self-reported questionnaires and taking into account several socio-demographic, lifestyle and health related characteristics. The 1,611 participants enrolled in our study. Anxiety was assessed by the Zung self-rating anxiety scale (SAS). A multivariate logistic regression model and restricted cubic spline with anxiety symptoms as the dependent variable were fitted. Results Of the T2DM patients in this study, 891 (55.31%) were male, 720 (44.69%) were female and 207 (12.85%) had anxiety symptoms. Controlling for potential confounders and intermediates, sleep duration >8 h relative to intermediate sleep (7–8 h) was significantly associated with anxiety syndrome (OR: 1.46, 95% CI [1.06–2.02], p = 0.02) and a J-shaped association was found between sleep duration and anxiety. The prevalence of anxiety symptoms was higher in the male group (>8 h/night) compared to the female. Study participants under the age of 50 who had a shorter sleep duration had a higher prevalence of anxiety compared to those between the ages of 50 and 60. Conclusion Among Chinese T2DM patients, there is a dose-response relationship between night sleep duration and anxiety, these findings may propose important public health implications for diabetes management.
Keywords: Anxiety; Diabetes mellitus, type 2; Sleep duration